A comparison of different unsteady flow control techniques in a highly loaded compressor cascade. (May 2019) - Zhang, Hongxin; Chen, Shaowen; Gong, Yun; Wang, Songtao
A numerical research is applied to investigate the effect of controlling the flow separation in a certain highly loaded compressor cascade using different unsteady flow control techniques. Firstly, unsteady pulsed suction as a new novel unsteady flow control technique was proposed and compared to steady constant suction in the control of flow separation. A more exciting effect of controlling the flow separation and enhancing the aerodynamic performance for unsteady pulsed suction was obtained compared to steady constant suction with the same time-averaged suction flow rate. Simultaneously, with the view to further exploring the potential of unsteady flow control technique, unsteady pulsed suction, unsteady pulsed blowing, and unsteady synthetic jet (three unsteady flow control techniques) are analyzed comparatively in detail by the related unsteady aerodynamic parameters such as excitation location, frequency, and amplitude. The results show that unsteady pulsed suction shows greater advantage than unsteady pulsed blowing and unsteady synthetic jet in controlling the flow separation. Unsteady pulsed suction and unsteady synthetic jet have a wider range of excitation location obtaining positive effects than unsteady pulsed blowing. The ranges of excitation frequency and excitation amplitude for unsteady pulsed suction gaining favorable effects are both much wider than that of unsteady pulsed blowing and unsteady synthetic jet. The optimum frequencies of unsteady pulsed suction, unsteady pulsed blowing, and unsteady synthetic jet are found to be different, but these optimum frequencies are all an integer multiple of the natural frequency of vortex shedding. The total pressure loss coefficient is reduced by 16.98%, 16.55%, and 17.38%, respectively, when excitation location, frequency, and amplitude are all their own optimal values for unsteady pulsed suction, unsteady pulsed blowing, and unsteady synthetic jet. The optimum result of unsteady synthetic jet only slightly outperforms that of unsteady pulsed suction and unsteady pulsed blowing. But unfortunately, there is no advantage from the standpoint of overall efficiency for the optimum result of unsteady synthetic jet because the slight improvement has to require a greater power consumption than the unsteady pulsed suction and unsteady pulsed blowing methods.